Pengaruh Celebrity Endorser dan Brand Image terhadap Minat Beli Kembali Dimediasi oleh Brand Trust pada Konsumen E-Commerce Tokopedia - Atthiyya Rizky Dhifanto Putri; Robertus Basiya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study aims to examine the influence of celebrity endorsers and brand image on repurchase interest mediated by brand trust. This type of research is quantitative research. The population of this study is all Tokopedia e-commerce consumers as many as 100 consumers. Data analysis techniques use descriptive analysis and multiple linear regression analysis. The results showed that celebrity endorsers were not significantly positive for brand trust, brand image was significantly positive for brand trust, celebrity endorsers were significantly positive for repurchase interest, brand image was significantly positive for repurchase interest, brand trust did not mediate the influence of celebrity endorsers on repurchase interest, brand trust was able to mediate the influence of brand image on repurchase interest, Brand trust is significantly positive about buyback interest.